Optimal Design of a New Aromatic Extractive Distillation Process Aided by a Co-solvent Mixture. (May 2017) - Wang, Q.; Zhang, B.J.; He, C.; He, C.C.; Chen, Q.L.
Abstract: Sulfolane Extractive Distillation (ED) processes are widely used for benzene, toluene and xylenes (BTX) separation. Based on the phase equilibrium data and NRTL property method, this paper develops an ED process aided by a co-solvent mixture of sulfolane, N-methyl-2-pyrrolidinone (NMP) and water to improve the recovery of aromatics and reduce the minimum hot utility requirement (Ht, min ). Firstly, the relative volatility of aromatics and non-aromatics are calculated and analyzed with the help of MATLAB and the results show that co-solvents have higher selectivity than NMP and higher dissolvability than sulfolane. In addition, a compressive simulation model and optimizing strategy for the new process are presented sequentially. In order to improve the accuracy of modelling, all of the missing parameters in the NRTL database are regressed from literature data or estimated using the Aspen Property Estimator. In particular, considering multi-variables and their interaction, a co-ordinative optimization strategy is proposed based on iterative optimization of local coupling parameters by taking Ht, min as the objective function. Meanwhile the energy consumption and separation efficiency are investigated through adjusting the key operating parameters of the ED process. The results show that the energy consumption of the ED process is significantly reduced and the recovery of aromatics increased from 99.69% to 99.92%.